Western Balkans Regular Economic Report, No. 14, Fall 2018 : Higher but Fragile Growth - World Bank Group (World Bank, Washington, DC, 2019)
Growth in the Western Balkans has strengthened to an estimated 3.5 percent. In most of the region, growth projections for 2018 have been revised upward. Growth was stimulated by higher public investment and consumption. Driven by tax reforms and faster growth, higher tax revenues created fiscal space, which some countries rushed to use for current spending and capital investment. Higher exports are also necessary for more secure long-term growth. External imbalances have been high but mostly stable. The risks clouding a positive growth outlook are both external and internal. A possible tightening of the financing conditions in international capital markets is a downside risk, especially in countries that have external and fiscal imbalances. With domestic sovereign bond markets often underdeveloped, Western Balkan countries are exposed to rises in global interest rates. Robust growth in the region also depends heavily on domestic and regional political stability, which define the speed of structural reforms. Mitigating these external and internal risks requires both a firm commitment to fiscal consolidation and acceleration of structural reforms.